Cancer in branchial cleft cyst - Wiśniewski, Tomasz; Ziółkowska, Ewa; Kubiak, Maria; Makarewicz, Roman (Contemporary Oncology/Współczesna Onkologia, 2011)
Branchial cleft squamous cell carcinoma is very rare and is a diagnostic and therapeutic challenge for the physician since it usually represents a cystic metastasis from an occult carcinoma. Various imaging modalities or even blind biopsies will help to identify the primary tumour. If the primary tumour is identified, an appropriate treatment decision can be made that incorporates both the primary tumour and the cervical node metastases. A 79-year-old male presented with a well-defined mass on the right side of the neck. The tumour was excised with the presumed diagnosis of lateral cervical cyst containing squamous cell carcinoma. After one year a carcinoma of the right tonsil developed. The patient was treated by surgery and adjuvant radiotherapy and he is doing well six months following the complete of treatment. The existence of branchiogenic carcinomas is questioned in this review, which also discusses the different possibilities in treatment.